2021
DOI: 10.21203/rs.3.rs-174454/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Directed evolution  improves the enzymatic synthesis of L-5-hydroxytryptophan by an  engineered tryptophan synthase

Abstract: L-5-Hydroxytryptophan is an important amino acid that is widely used in food and medicine. In this study, L-5-hydroxytryptophan was synthesized by a modified tryptophan synthase. A direct evolution strategy was applied to engineer tryptophan synthase from Escherichia coli to improve the efficiency of L-5-hydroxytryptophan synthesis. Tryptophan synthase was modified by error-prone PCR. A high activity mutant enzyme (V231A/K382G) was obtained by a high-throughput screening method. The activity of mutant enzyme (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…A large number of engineering applications and measurements have indicated that there is significant randomness and variability in both load and resistance. The uncertain statistical parameters of loads according to the provisions of "Unified Standard for Reliability Design of Building structures" GB50068-2018 [4], "Code for load of Building structures" GB50009-2012 [25], and "Technical Specification for Spatial Grid structures" JGJ7-2010 [33] are shown in Table 1.…”
Section: Load and Resistance Uncertaintymentioning
confidence: 99%
See 1 more Smart Citation
“…A large number of engineering applications and measurements have indicated that there is significant randomness and variability in both load and resistance. The uncertain statistical parameters of loads according to the provisions of "Unified Standard for Reliability Design of Building structures" GB50068-2018 [4], "Code for load of Building structures" GB50009-2012 [25], and "Technical Specification for Spatial Grid structures" JGJ7-2010 [33] are shown in Table 1.…”
Section: Load and Resistance Uncertaintymentioning
confidence: 99%
“…As the service life of a large number of steel structures progresses, durability issues [1][2][3] related to corrosion problems come to the fore [4,5]. However, there are no operational assessment and design correction methods that take into consideration the development and effects of corrosion under different environments.…”
Section: Introductionmentioning
confidence: 99%